A million-channel CO-PrOx microreactor on a fingertip for fuel cell application - Divins, N. J. (2011)
A silicon micromonolith containing ca. 40000 regular channels of 3.3μm in diameter per square millimeter has been successfully functionalized with an Au/TiO2 catalyst for CO preferential oxidation (CO-PrOx) in the presence of hydrogen. The functionalization of the silicon microchannels has been accomplished by growing a SiO2 layer on the channel walls, followed by exchange with a titanium alkoxyde precursor and decomposition into TiO2 and, finally, by anchoring carbosilanethiol dendron protected pre-formed Au nanoparticles. Catalytically active centers at the Au-TiO2 interface have been obtained by thermal activation. With this method, an excellent homogeneity and adherence of the catalytic layer over the microchannels of the silicon micromonolith has been obtained, resulting in geometric exposed surface area values of about 4×105m2/m3. The functionalized silicon micromonolith has been tested for CO-PrOx at 363-433K and λ=2 under H2/CO=0-20 (molar), and the results have been compared with those obtained over a conventional cordierite monolith with 400cpsi loaded with the same catalyst. The performance of the silicon micromonolith, which converts ca. 1NmL of CO per minute and mL of microreactor at 398K under H2/CO ∼20, is two orders of magnitude higher than that of conventional monolithic structures, suggesting that silicon micromonoliths could be particularly effective for hydrogen purification in low-temperature microfuel cells for portable applications. © 2010 Elsevier B.V.